Water quality analysis during tidal conditions using the Pollution Index Method in the Karang Mumus River, East Kalimantan - Prasetyo, Wahyu Agus; Hamdhani, Hamdhani; Mustakim, Mohammad (Faculty of Fisheries and Marine Science, Mulawarman University, 2025)
The Karang Mumus River, located in East Kalimantan, serves as an essential resource for the local community, supporting fisheries, trade, and household activities. However, these uses contribute to waste accumulation, potentially impacting the river's water quality. Tidal movements play a crucial role in water circulation, with the river's flow influenced by the Mahakam River’s tides, leading to backwater flow during high tide. This tidal phase affects the dispersion of pollutants. This study aims to assess the water quality, Pollution Index, and variations in water conditions between high and low tide in the Karang Mumus River. Sampling was conducted at three research stations: Station 1 (Gelatik Bridge), Station 2 (Perniagaan Bridge), and Station 3 (Selili Bridge) from September to November 2023. Water quality measurements were performed both in situ (on-site) and ex situ (at the Water Quality Laboratory, Faculty of Fisheries and Marine Science, Mulawarman University). The analysis follows Government Regulation (PP) No. 22 of 2021 on Environmental Protection and Management (Appendix VI). Results indicate that the DO and COD parameters only meet class III-IV water quality standards, while color, temperature, TDS, TSS, BOD, total phosphate, and nitrate comply with class I-IV standards. The Pollution Index (IP) assessment, based on class I-IV quality standards, categorizes the Karang Mumus River as meeting quality standards to lightly polluted, with an IP range of 0.53 - 2.90. According to Minister of Environment Decree No. 115 of 2003, water meeting quality standards has an IP of 0 < IP < 1.0, while lightly polluted water falls within 1 < IP < 5.